Kursi Dan Eksistensinya Dari Masa Ke Masa - -, Indarto (Pendhapa, 2009)
A chair is a culture product as well as a social product. A chair is a means or a tool for sitting for human being. A chair has better luck than other kinds of furniture have. A chair has the most prestigious symbolic meaning which other furniture or designed artifact does not have. The word ‘Kedudukan’ (occupation) which comes from the root ‘duduk’ (to sit) means power so that it is no wonder that a chair becomes the symbol of power. A chair as a tool for sitting has developed to be a cross-cultural and country mass product since Industrial Revolution in England. A modern chair designed to be comfortable from an ergonomic standpoint, to be functional from the standpoint of shape, and to be economical from the standpoint of production has rapidly developed and many people are interested in it.Key words: chair, symbol of power, modern, shape